EFFECTS OF TYROSINE AND PLANT GROWTH REGULATORS ON GROWTH AND DEVELOPMENT OF GLORIOSA SUPERBA LINN., A MEDICINAL PLANT, IN VITRO - Muangsan, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The study of effects of tyrosine and plant growth regulators on rhizome cultures was carried out on modified Murashige Skoog medium. The sterile rhizomes were cut and cultured on MS medium, supplemented with 1 mg/l 2,4-D, 1 mg/l BA and various concentrations of tyrosine under light and dark condition. The experimental data showed that the highest percentage of callus formation was on the medium with 50 mg/l tyrosine, in the dark condition (100%) and in the light condition (85%). The average fresh weight of callus cultured in the dark for 16 weeks was 6.25 g. Shoot induction was performed using the combination of NAA and BA for 36 weeks. The experimental data revealed that the shoot regeneration from callus was 100% on the medium with 4 mg/l BA and 4 mg/l NAA. Comparison among various concentrations of BA and NAA showed that shoot formation was 83% and 50% on the medium containing 4 mg/l BA and 4 mg/l kinetin, respectively. The chromosome number from the root tip obtained from the tissue culture was 2n = 22. Acknowledgements: Dept. of Biology, Khon Kaen University provided funding and all participants in this project.